Assessment of Sub-Chronic Toxicity of a Polyherbal Infusion of Peperomia pellucida, Moringa oleifera, and Biancaea sappan in Male Mice (Mus musculus) - Akbar, Heldi Fadillah; Mahmudah, Febrina; Ahmad, Islamudin (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2026)
This study evaluated the sub-chronic toxicity of a polyherbal infusion composed of Peperomia pellucida, Moringa oleifera, and Biancaea sappan in male mice. Thirty healthy male mice aged 6–8 weeks, weighing 20–30 g, were orally administered doses of 560, 650, and 1300 mg/kg body weight daily for 28 days, with satellite groups observed for up to 42 days. Clinical monitoring and body weight measurements revealed no signs of toxicity or growth impairment. However, organ index analysis demonstrated dose-dependent increases in liver and kidney weights, and histopathological examination confirmed hepatocellular degeneration and tubular damage at the highest dose. These findings indicate that the infusion is generally safe at low to moderate doses, but prolonged high-dose consumption may compromise hepatic and renal integrity. The study provides important toxicological evidence supporting the establishment of safe dosage ranges for polyherbal formulations and contributes to the scientific validation of traditional medicine practices.